Modelling and analysis of linear DC motor with constant thrust characteristics - Othman, Raja Nor Firdaus Kashfi Raja; Isa, Siti Zulaika Mat; Zuki, Nor Aishah Md.; Ahmad, Suhairi Rizuan Che; Shukor, Fairul Azhar Abdul; Othman, Md. Nazri (Institute of Advanced Engineering and Science, 2025)
This paper introduces a portable and user-friendly innovation in food processing by replacing traditional molding methods with a linear DC motor (LDM). Traditional methods, which involve manual pressing, are energy-intensive and time-consuming, reducing productivity. The proposed LDM offers a simple, cost-effective, and robust solution capable of producing constant thrust, unlike conventional LDMs that require complex and expensive control methods and are limited to short displacements. The research focuses on modelling and analyzing an LDM with constant thrust characteristics for food processing applications. The primary objective is to model the thrust using the permeance analysis method (PAM), ensuring constant thrust capability. Verification was conducted using the finite element method (FEM) and measurement results, showing a percentage difference of 1.7% and 6.5%, respectively, between PAM and the other methods. The study provides valuable guidance for designing LDMs with constant thrust capabilities, enhancing the efficiency and practicality of food processing devices.